Code Of Conduct (Code) Yunior Tennis Tournament In Athlet National Tenis Tournament TDP Bupati Solok Cup 2019 - rezki rezki (Jurnal Berkarya Pengabdian Masyarakat, 2019)
The period of mining development in the tennis sports is increasingly mushrooming. This is marked by the increasing number of tournaments both senior and Junior. Included in the Sumatra region itself. To become a professional player needs to be continuous in participating in the tournament, so athletes can continue to evaluate and measure their achievements. To deal with the tennis tournament recognized by PELTI, a player must obey the rules and Code of Conduct (Code) rules and order in the competition. One of the most basic things as an athlete is regarding the Code of Conduct (Code). Not many junior players know about the Tennis Court Code of Conduct (Code) and sometimes organizers and organizations forget this. For this reason, it is necessary to socialize about the code of ethics, so that players will get used to from the junior to participate in the tournament properly. Activities include " Code of Conduct (Code) for the Tennis Tennis Youth Tournament at the Solok Regent Tennis National Championship in 2019". This activity was held on 4 and 5 April 2019 in Kubung sub-district, Solok district, West Sumatra. The activity was attended by 40 National Junior Players who competed in the National Tennis Championship in the Solok II Regent Cup in 2019.